Visual motor integration, visual perception and motor coordination in children with horizontal strabismus - Meng, Edwin Pheng Chin (2023)
Introduction Strabismus refers to misalignment of the eyes, in which the eyes are pointing in different directions. This condition has many health and social implications which may disrupt normal development in a child. Visual motor integration, the ability of a person to perceive visual input and coordinate a motor response, is an essential skill to learn and master in a normal developing child. Exploring the visual motor integration of children with strabismus may allow healthcare providers to provide crucial services to these children. Objective This cross-sectional study aims to evaluate visual motor integration of children 6 to 17 years old with and without horizontal strabismus. Methodology A total of 90 children were recruited in this study (control vs test group). The ability of a child to integrate their visual and motor abilities was recorded using The Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery-VMI) with the supplemental Developmental Tests of Visual Perception and Motor Coordination. The scores between both groups were analysed using independent t-test and one way analysis of covariance. Results There were significant differences in the mean Berry-VMI score between children with horizontal strabismus and children without strabismus (p<0.001). Similarly, the visual perception score and motor coordination score in children with strabismus was significantly lower than in children without strabismus (p<0.001). These differences persisted even after adjustment for age, gender, favorite sport activities, number of siblings and the presence of stereopsis. Conclusion The mean score of children with horizontal strabismus is significant lower in Beery-VMI, Visual Perception and Motor Coordination when compared with children with normal eye alignment, even after adjustment for potential confounding factors. These finding give us an insight that children with strabismus may require extra attention and services to improve their visual motor integration compared to normal children.